Comparison between butorphanol and nalbuphine for alleviation of catheter-related bladder discomfort and emergence agitation in patients undergoing open spinal surgery: a randomized clinical trial - Weilian Wang; Chang Zhang; Qian Zhou; Jiapeng Dan; Kun Zhang; Ting Zheng (Annals of Medicine, 2025)
Introduction Opioid receptor agonist/antagonists have positive effects in the management of catheter-related bladder discomfort (CRBD). Whether the differences in κ receptor affinity will have different effects is still unknown. This study aims to compare the efficacy of opioid agents with varying κ receptor affinity profiles in alleviating CRBD and emergence agitation (EA).Patients and Methods A total of 120 patients undergoing open spinal surgery were randomly assigned into three groups: saline group, butorphanol group, and nalbuphine group. All drugs were injected intravenously 30 min before the end of surgery. The primary outcomes were the incidence of moderate to severe CRBD and EA at 5 min after tracheal extubation. Secondary outcomes included the severity of CRBD, numerical rating scales (NRS), Richmond agitation-sedation scale (RASS) at five time points after tracheal extubation, the need for rescue analgesia and the incidence of adverse events were also recorded.Results The incidence of moderate to severe CRBD was significantly lower in group B compared to group C (p < 0.001) at all the time points. Group B had significantly fewer patients with severe CRBD and lower NRS scores than both groups C and N (p < 0.001) at T1 and T2. Group B had lower RASS scores than groups N and C at T1, while at T2, T3 and T4, groups B and N continued to exhibit significantly lower NRS scores compared to group C (p < 0.001). The requirement for rescue analgesia decreased sequentially from group C to group N and then to group B (p < 0.001). The incidence of EA was significantly lower in groups B and N than in group C (p < 0.001).Conclusions Opioid receptor agonist/antagonists demonstrate efficacy in preventing CRBD and EA without significant adverse events. Butorphanol exhibits superior efficacy to nalbuphine in the early postoperative period.